WHY ENGLISH IS A GLOBAL LANGUAGE - Safarova Guli Sherzod qizi (International Journal of Literature and Language Studies, 2026)
English has become the most widely used international language in the modern world. It serves as a common means of communication among people who have different native languages and cultural backgrounds. Today, English is used in education, business, science, technology, diplomacy, tourism, entertainment, and digital communication. Although thousands of languages are spoken across the globe, English has gained a unique position because it enables people to exchange knowledge, cooperate internationally, and access global opportunities. This paper examines the historical development of English, the reasons behind its global status, and its influence on different areas of modern life. It also discusses the challenges associated with the worldwide spread of English and considers its future role in an increasingly interconnected world.